2011
DOI: 10.1002/hec.1776
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Insurance Mandates on Choices and Outcomes in Infertility Treatment Markets

Abstract: SUMMARYFor the 10% to 15% of American married couples who experience reproductive problems, in vitro fertilization (IVF) is the leading technologically advanced treatment procedure. However, IVF's expense may prevent many couples from receiving treatment, and those who are treated may take an overly aggressive approach to reduce the probability of failure. Aggressive treatment, which occurs through an increase in the number of embryos transferred during IVF, can lead to medically dangerous multiple births. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 27 publications
(36 reference statements)
1
84
0
1
Order By: Relevance
“…Remarkably, this finding holds even after accounting for important factors such as GDP per capita, the number of physicians, and the number of ART clinics in a country. Studies that have looked at variation within countries and over time (e.g., Hamilton and McManus 2012) have also found evidence that affordability is an important driver not only of utilization, but also of the use of safer ART practices. Norms and beliefs also seem to play an important role for cross-national differences in ART usage.…”
Section: Usage Of Assisted Reproductive Technologies In European Counmentioning
confidence: 99%
“…Remarkably, this finding holds even after accounting for important factors such as GDP per capita, the number of physicians, and the number of ART clinics in a country. Studies that have looked at variation within countries and over time (e.g., Hamilton and McManus 2012) have also found evidence that affordability is an important driver not only of utilization, but also of the use of safer ART practices. Norms and beliefs also seem to play an important role for cross-national differences in ART usage.…”
Section: Usage Of Assisted Reproductive Technologies In European Counmentioning
confidence: 99%
“…Chambers et al (2013) have commented that the financial context of infertility treatment has a substantial effect on the acceptability of elective SET to patients, 'presumably because more affordable treatment reduces the financial incentive to achieve pregnancy in the shortest number of treatment cycles.' In the USA, with the variability of insurance coverage for infertility treatment, the resulting high cost may encourage particular practices, such as transferring more embryos (Hamilton and McManus, 2012). These authors found that insurance mandates (i.e.…”
Section: Multiple Birthsmentioning
confidence: 99%
“…Concerns about policy endogeneity have been discussed in previous studies, such as Bitler and Schmidt (2012) and Hamilton and McManus (2012). The latter two studies in particular reached the conclusion that the enactment of infertility treatment mandates was largely the result of the efforts of a national infertility association (RESOLVE) and the political rather than fertility preferences of state residents.…”
Section: Introductionmentioning
confidence: 96%
“…For example, in 1992, a birth from an IVF procedure cost between 44,000 and 211,942 USD (Neumann et al 1994). Over time, however, ART patients have faced substantially lower costs due to increased competition (Hamilton and McManus 2012), a reduced number of cycles due to better technology, 1,2 and most importantly, the availability of insurance in both the United States and in Europe. 3 In this paper, we analyse whether easier access to ARTs induces women to delay motherhood and whether, in the long term, it affects women's completed fertility by the end of their reproductive lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation